The Impact of E-WOM (Electronic Word of Mouth) on Purchase Decisions on the Shopee Platform - Reni Silvia Yuli Safitri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The growth of digital business in today’s era influences consumer behavior, particularly when it comes to making decisions about purchasing or consuming a product; trust in Electronic Word of Mouth (e-WOM) has become a key factor in helping consumers make the right decisions regarding product consumption. This study aims to analyze the influence of E-WOM (Electronic Word of Mouth) on purchasing decisions on the Shopee platform. The study employs a qualitative research method and uses literature review as the data collection technique. The results indicate that E-WOM influences purchasing decisions and can reduce purchasing risk by helping consumers mitigate the risk of product defects or evaluate product quality before making an online purchase.